Prototipe Otomatisasi dan Pemantauan Sistem Hidroponik Berbasis IoT dengan Pemanfaatan Solar Panel Sebagai Sumber Energi - Apta Prana Mas Erlangga; Ketut Saha Kesta Dinatha; Frisca Elfrisa Nainggolan; Soni Prayogi (G-Tech: Jurnal Teknologi Terapan, 2023)
This research presents a prototype of automation and monitoring of an Internet of Things (IoT) based hydroponic system that is optimized by utilizing solar panels as an energy source. This system is designed to increase the efficiency of modern hydroponic farming by monitoring and controlling environmental parameters such as humidity levels, temperature, pH, and plant lighting in real time. Solar panels are used to provide a sustainable source of energy, making the system eco-friendly and autonomous. This prototype is connected to an IoT platform that allows users to access and control the system via a smartphone or computer application. In addition, the collected environmental data can be analyzed to increase agricultural yields and minimize resource consumption. This research represents an essential step in combining IoT technology and renewable energy to increase the productivity of modern agriculture in a sustainable and efficient way.